2016
DOI: 10.1007/s10549-016-3859-z
|View full text |Cite
|
Sign up to set email alerts
|

Ages at menarche- and menopause-related genetic variants in relation to terminal duct lobular unit involution in normal breast tissue

Abstract: Purpose Reduced levels of terminal duct lobular unit (TDLU) involution, as reflected by higher numbers of TDLUs and acini per TDLU, have been associated with higher breast cancer risk. Younger age at menarche and older age at menopause have been previously related to lower levels of TDLU involution. To determine a possible genetic link, we examined whether single nucleotide polymorphisms (SNPs) previously established in genome-wide association studies (GWAS) for ages at menarche and menopause are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Elks et al (Elks et al, 2010) also suggested contribution of this SNP to height based on the GIANT consortium data. Oh et al (Oh et al, 2016) reported association of rs6438424 with the breast tissue development.…”
Section: Discussionmentioning
confidence: 99%
“…Elks et al (Elks et al, 2010) also suggested contribution of this SNP to height based on the GIANT consortium data. Oh et al (Oh et al, 2016) reported association of rs6438424 with the breast tissue development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological impact of the SNP on gene expression and the mechanism of RXRG in regulating reproductive aging, remain unclear. In a recent study, rs466639 was associated with involution of terminal duct lobular unit (TDLU), the milk-producing structures of the breast[ 48 ]. The variant T allele associated with earlier AM was also associated with a higher count of TDLU, which is a recognized risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because SNPs examined in this analysis are well‐established breast cancer susceptibility loci, we used a threshold of p < 0.05 to define significant associations. Since our power to test for individual associations was limited, we also tested for enrichment of associations between SNPs and measures of TDLU involution . We did this using binomial tests in two ways: ( i ) comparing the proportion of the SNP associations (regardless of statistical significance) in the direction consistent with our expectation (RR > 1.0) based on the relationship of the SNPs with breast cancer to 50%, which is what would have been expected by chance; and ( ii ) comparing the proportion of SNPs with significant associations to 5%, which is expected by chance alone.…”
Section: Methodsmentioning
confidence: 99%